A Load Balancing Algorithm for Layer 2 Routing Based Wi-SUN Systems - Habara, Takuya; Mizutani, Keiichi; Harada, Hiroshi (2017 IEEE 85th Vehicular Technology Conference (VTC Spring), 2017)
This paper proposes a load balancing algorithm for a layer 2 routing (L2R) protocol of IEEE 802.15.4/4g/4e based wireless smart utility network (Wi-SUN) systems to achieve low-power consumption mesh networking. In the conventional link quality based routing method scheme discussed in IEEE 802.15.10 Draft 01, the fairness of cumulative number of sending packets has not effectively been achieved. Therefore, it may cause that many terminals send packets to a certain terminal. In the proposed method, the number of sendings is used to select the path of routing as well as link quality. The performance of the proposed routing method is evaluated by computer simulation. As the result, the proposed scheme can improve the maximum sending ratio that evaluates the cumulative number of sending packets by 59% with no degradation of the average sending times and end-to-end success rate (E2E-SR) compared with the conventional routing scheme that is one of the candidate schemes discussed in IEEE 802.15.10 Draft 01.